Discovering the link between IL12RB1 gene polymorphisms and tuberculosis susceptibility: a comprehensive meta-analysis - Huang, Jie; He, Qiurong; Huang, Lijun; Liu, Liping; Yang, Pei; Chen, Min (Frontiers in Public Health, 2024)
Numerous studies suggest that the risk of tuberculosis (TB) is linked to gene polymorphisms of the interleukin-12 receptor b subunit 1 (IL12RB1), but the association between IL12RB1 polymorphisms and TB susceptibility has not been thoroughly investigated. Therefore, a meta-analysis was conducted based on eight case-control studies with 10,112 individuals to further explore this topic. A systematic search of PubMed, Web of Science, Excerpt Medica Database, and Google Scholar up until April 6th, 2023 was performed. ORs and 95% CIs were pooled using the random-effect model. The epidemiological credibility of all significant associations was assessed using the Venice criteria and false-positive report probability (FPRP) analyses. The IL12RB1 rs11575934 and rs401502 showed solid evidence of no significant association with TB susceptibility. However, a weak association was observed between the IL12RB1 rs375947 biomarker and pulmonary tuberculosis (PTB) susceptibility (OR = 1.64, 95% CI: 1.22, 2.21). These findings should be confirmed through larger, better-designed studies to clarify the relationship between biomarkers in IL12RB1 gene and different types of TB susceptibility.